An essay on participation and political consciousness: Un ensayo sobre la participación y la conciencia política - Cronick, Karen (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
The main objective of this essay is to review how community and citizen participation can facilitate the development of democracy, and limit the power of tyrannical systems. In the following pages I have examined the concept of participation as described in psychological and philosophical literature in order to demonstrate how open debates regarding communities’ normative values can mobilize efforts to create more inclusive and engaged cultures in groups, societies and governments. I illustrate how this process happens and give theoretical arguments for promoting it.